Effects of spur dikes on hydraulic and morphological characteristics of anabranching channels - Alsawaf, Mena Ahmed Dawad (2018)
Anabranches are multi-thread channels divided by at least one mid-channel bar. Even though they are a dominant pattern in natural streams, their hydraulic and morphological properties have not been well understood due to their variability and complexity, as well as there have been only limited studies to examine the effects of any hydraulic structure in these channels. Human activities in anabranches may cause aggravation in sedimentation problem and disturb the flow regime within the region, which require restoration works to reverse its effects or improve the river characteristics. Spur dikes are eco-friendly structures that are normally used to modify the flow in channels. The aim of this study is to investigate experimentally the hydraulic behaviour and morphological profiles that resulted from the action of spur dikes on the flow in anabranches. 93 tests were carried out in three main segments. Firstly, spur dikes of various lengths, alignments, shapes, numbers and permeability were studied in an anabranch with a single bar. Secondly, perpendicular spur dikes were studied in anabranches with different bar sizes, and finally, a perpendicular spur dike placed at different locations relative to a bar were studied in anabranches with a single or double bars. In some cases, five flowrates were used, while in others just two flowrate values were used. All experiments were performed under clear water condition using uniform fine sand. Acoustic Doppler Velocimeter (ADV) and ultrasonic flowmeter were used to measure the velocities and flowrates, respectively. The main results show, when 'the angle of the spur dike is 90° or less (measured in the direction of flow) and its location is at upstream of the bar or when the length of the bar is decreased, the flowrate proportion in the active branch (the channel that carry more than 50% of the main flow rate) is increased. The flow could increase up to 48% while the velocity could be 35% higher than the case without the spur dike. On the other hand, a spur dike located downstream reduces the velocity in the anabranches up to 23% lower than the case without the dike. It was also found that in this case, while spur dike protects the bar against erosion, it causes the largest scour at its head. The flow reattachment area behind the spur dike and the eddy at the bar tail playa crucial role to the flow proportions in both branches, in the cases when the bar lengthto- width ratio is 3 or less. The biggest diffusion spots of energy in between the branches were created by a dike located in the middle of the anabranches. The magnitude of maximum velocity in the direction of the incoming flow acting on a bar is the main driver to control the erosion process. The curved spur dike and the installation of two spur dikes at the upper and lower ends of an anabranch caused a higher erosion in the submerged part of the bar, which reached up 10 -+000 with a full erosion to the apparent part when the anabranch is symmetric. The erosion reached 84% for the submerged part of the bar when a dike is placed at the opposite side of the narrow branch when the anabranch is asymmetric. Shields shear stress of the advancing flow that faces the bar can be used as an indication of the bar stability against erosion, that is when it is lower than the threshold value of5.25. it is unstable. The dike effect in diverting the flow extends longer the case when there are two bars in the anabranches compared to just one bar. An equation has been derived to estimate the extent of erosion of the apparent bar with time. Subsequently, the experimental results of this study were employed to propose solutions for some common scenarios of river degradation. Deflecting spur dike could be used to accelerate the erosion of the mid-channel bar, while to decelerate the erosion process. the dike should be located at the confluence section. To provide a suitable condition for navigat ion. curved dike located upstream or two repelling dikes should be located at the upstream and downstream sections of anabranches. Lastly, to promote a condition that satisfies the requirements for a balanced eco-system. two successive dikes at the upstream section of the anabranches should be constructed.